Basic Nutrient Requirements of Beef Cows - Matt Hersom (EDIS)
AN190, an 11-page fact sheet by Matt Hersom, discusses the basic nutrients that are required for production and provides tables indicating diet concentration and daily intake requirements of key nutrients for beef cattle. The information contained in this publication is based upon the recommendations published in the Nutrient Requirements of Beef Cattle (2000). Published by the UF Department of Animal Science, October 2007.